Sellar-Parasellar and Petrous Bone Metastasis from Differentiated Thyroid Carcinoma: Imaging Characteristics and Follow-Up Profile Post Radioiodine Therapy - Sonavane, Sunita Nitin; Upadhye, Trupti; Basu, Sandip (World Journal of Nuclear Medicine, 2023)
Sella turcica and petrous bone metastasis from differentiated thyroid carcinoma are rare clinical entities, with only a few limited cases reported to date. Two cases, one of sella turcica metastasis and the other of petrous bone metastasis from carcinoma of the thyroid gland, are presented. The cases diagnosed to have arisen from poorly differentiated thyroid carcinoma and follicular carcinoma of thyroid, respectively, subsequently underwent total thyroidectomy, radioiodine (RAI) scans and RAI therapies with iodine-131, external radiotherapy, and levothyroxine suppression with follow-up. Their clinical symptoms gradually subsided, with reduction in serum thyroglobulin, and finally resulted in disease stabilization. With the multimodality therapeutic approach, both patients are alive to date, with 48- and 60-month survival post diagnosis, respectively.
Keywords: sella; petrous apex; differentiated thyroid cancer; FDG; radioiodine; planar; SPECT/CT; PET/CT